Agency Theory Dalam Keputusan Keuangan: Sebuah Tinjauan Teoritis - Christian Herdinata (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
Agency Theory bases its contractual relationships between principals and agents. Principal is the party that mandates the agency to act on behalf of the principal, while the agent is given the assignment by the principal to run the company. This study explains more about the agency theory in financial decision. Themanagement (agents )in performing the operation should give priority to the interests of the owner of the company by increasing the prosperity of the shareholders, but management will often have different interests with shareholder interests, giving rise to conflicts of interest between management and shareholders. Therefore, the necessary mechanisms to control agency conflicts that occur: first, increase company stock ownership by management and secondly,increased financing with debt; third, with monitoring by institutional investors, and the fourth, Dividend Payout Ratio via increased (DPR) or the ratio of dividends to net income are thus not enough free cash flow and forced to mancari management of external funding to finance its investment.